Training On Science Laboratory Management And Maintenance For Junior High School Teachers In East Aceh - Tri Mustika Sarjani; Amin Harahap (CV. AFDIFAL MAJU BERKAH, 2023)
The East Aceh IPA MGMP consists of 24 sub-districts with 221 schools. The selection of service areas is represented by three regions, namely Idi Rayeuk District, Darul Aman District, and Darul Ihsan District. East Aceh IPA MGMP teachers are still experiencing problems in terms of knowledge and skills in managing laboratories, using tools and materials as well as in equipment maintenance. The service activity aims to provide knowledge and skills for MGMP IPA teachers in East Aceh Regency. The method used is a descriptive method to see the improvement of teacher skills in compiling laboratory SOPs, maintenance of laboratory equipment and materials.